2014
DOI: 10.1016/j.jped.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dietary patterns of adolescents attending public schools

Abstract: deviations from the "healthy" patterns were not associated to low income, but rather to bad eating habits in the studied population. Overweight adolescents did not adhere to the "healthy" dietary pattern, emphasizing the need for nutritional education among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 19 publications
3
49
0
5
Order By: Relevance
“…The "fast food snacks" pattern, including soft drinks, sweets, cakes, cookies, salted snacks, processed meats, and other high-fat products, also identified in other studies 47,49,50,51 , showed positive and moderate associations in all the target pairs. This finding may indicate the Westernization of eating habits in the family, since this pattern consists of foods that are high in fat, sugar, and salt, reflecting the incorporation of unhealthy habits and customs related to the Western lifestyle 52,53,54,55 , especially in Brazilian families with adolescent children, given that consumption of such foods is more prevalent in this age bracket 48 .…”
Section: Discussionsupporting
confidence: 68%
“…The "fast food snacks" pattern, including soft drinks, sweets, cakes, cookies, salted snacks, processed meats, and other high-fat products, also identified in other studies 47,49,50,51 , showed positive and moderate associations in all the target pairs. This finding may indicate the Westernization of eating habits in the family, since this pattern consists of foods that are high in fat, sugar, and salt, reflecting the incorporation of unhealthy habits and customs related to the Western lifestyle 52,53,54,55 , especially in Brazilian families with adolescent children, given that consumption of such foods is more prevalent in this age bracket 48 .…”
Section: Discussionsupporting
confidence: 68%
“…A cross-sectional study performed in the state of Minas Gerais, Brazil, in 2011, involving 523 adolescents found no association between the traditional pattern (rice, beans, meat, vegetables, eggs and juice) and overweight/ obesity [37]. Rice, beans and meat are part of the dietary habit of the Brazilian population and are considered markers of a healthy diet.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were all cross-sectional studies, with the exception of one case-control study. 70 The studies were conducted in nine different countries and the majority of studies were from Asian countries (Iran, 70 China, 61,65,66,69,71 and Lebanon 64,67 ), with four from American countries (Mexico, 58 Brazil, 60,63 and Colombia 62 ), two from European countries (Norway 57,59 ), one from Australia, 19 and one from Polynesia (Samoan island of Upolu 68 ).…”
Section: Study Characteristicsmentioning
confidence: 99%